ANALISIS KELAYAKAN USAHA GULA KELAPA DI KAMPUNG KUMBE DISTRIK MALIND KABUPATEN MERAUKE - Indrawati Anitu; Ineke N. Widyantari; Maria M. D Widiastuti (Universitas Musamus, Merauke, Papua, 2017)
This study aims to determine and analyze the feasibility and profitability of palm sugar production in Kumbe village, Malind district, Merauke regency. This research conducted for two months, from May to June 2016. The sample using cencus technique. All the population of palm sugar production become respondent. The analysis data used benefit and cost ratio in palm sugar production by using quantitative and qualitative data. This technique using data of costs, benefits and feasibility of palm sugar. The result showed that total average revenue is Rp. 28,521,000.00 and total average cost is Rp. 40,950,473.21, so the total average profit is Rp. 48,570,526.79. Palm sugar production in Kumbe village feasible become a unit business, with rasio R/C 2.19. It is means that every Rp. 1,00 will provide the benefits 2.19 times the costs incurred.